2015
DOI: 10.1038/bcj.2015.88
|View full text |Cite|
|
Sign up to set email alerts
|

Loss in MCL-1 function sensitizes non-Hodgkin’s lymphoma cell lines to the BCL-2-selective inhibitor venetoclax (ABT-199)

Abstract: As a population, non-Hodgkin's lymphoma (NHL) cell lines positive for the t(14;18) translocation and/or possessing elevated BCL2 copy number (CN; BCL2High) are exquisitely sensitive to navitoclax or the B-cell lymphoma protein-2 (BCL-2)-selective inhibitor venetoclax. Despite this, some BCL2High cell lines remain resistant to either agent. Here we show that the MCL-1-specific inhibitor A-1210477 sensitizes these cell lines to navitoclax. Chemical segregation of this synergy with the BCL-2-selective inhibitor v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 53 publications
(86 reference statements)
9
74
0
Order By: Relevance
“…For instance, targeting additional antiapoptotic proteins known to cause resistance to venetoclax (eg, MCL1 or BCL-XL) may be required. 95,96 Targeting MYC may be helpful, but identifying specific inhibitors to MYC protein has been an ongoing challenge, as reviewed in McKeown and Bradner. 97 MYC has a shorter half-life than BCL2 (;4 vs ;24 hours), and inhibiting translation or transcription is effective in treating Em-Myc lymphomas.…”
Section: 89mentioning
confidence: 99%
“…For instance, targeting additional antiapoptotic proteins known to cause resistance to venetoclax (eg, MCL1 or BCL-XL) may be required. 95,96 Targeting MYC may be helpful, but identifying specific inhibitors to MYC protein has been an ongoing challenge, as reviewed in McKeown and Bradner. 97 MYC has a shorter half-life than BCL2 (;4 vs ;24 hours), and inhibiting translation or transcription is effective in treating Em-Myc lymphomas.…”
Section: 89mentioning
confidence: 99%
“…Certain t(14;18)-positive cell lines such as SU-DHL-4, although high BCL-2 expressers, have been demonstrated to be resistant to venetoclax due to MCL-1 expression. In these cases, adding a CDK9 inhibitor (alvocidib/flavopiridol) or a direct inhibitor of MCL-1 (A-1210477) to venetoclax leads to synergistic cell killing (65). Additional synergies may also exist with other pathways known to promote tumor cell survival, as has been reported using the dual PI3K/mTOR (mammalian target of rapamycin) inhibitor BEZ235 and venetoclax (66).…”
Section: Identifying Sensitive Tumor Types and Likely Respondersmentioning
confidence: 99%
“…By inhibiting MCL-1, A-1210477 was shown to interact synergistically with the BCL-2/BCL-xL inhibitor ABT-263 (navitoclax) to kill a variety of cancer cell types (34)(35)(36). We found that the combination of A-1210477 and cobimetinib was synergistic as shown by a mechanism that involved disruption of the interaction of MCL-1 with the pro-apoptotic BH3-only proteins BIM and BAK by A-1210477, and by the ability of cobimetinib to suppress MCL-1 and induce BIM expression.…”
Section: Discussionmentioning
confidence: 99%